2004
DOI: 10.1007/b11310
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Spectroscopy and Photochemistry of the [M(η5-C5H5)(CO)2]2 Complexes (M=Fe, Ru)

Abstract: The structures of all possible isomeric forms of the [M(h 5 -C 5 H 5 )(CO) 2 ] 2 complexes (M=Fe, Ru) are calculated with the use of the DFT method. The results indicate that both dimers can occur in three stable forms: bridged trans and cis and non-bridged trans. Contrary to the previous reports, the cis non-bridged form turns out to be an unstable transition state. Instead, an additional stable structure, a gauche non-bridged one, is found but only in the case of the Ru compound. Without any outer-sphere int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…[1][2][3][4] The CpFe(CO) 2 dimer ([CpFe(CO) 2 ] 2 or Cp 2 Fe 2 (CO) 4 ), as a typical transition metal carbonyl complex, has been investigated for many years. 5,6 It is known that the CpFe(CO) 2 dimer can adopt multiple isomeric forms in solution. [7][8][9] The structures of two dominant isomers are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The CpFe(CO) 2 dimer ([CpFe(CO) 2 ] 2 or Cp 2 Fe 2 (CO) 4 ), as a typical transition metal carbonyl complex, has been investigated for many years. 5,6 It is known that the CpFe(CO) 2 dimer can adopt multiple isomeric forms in solution. [7][8][9] The structures of two dominant isomers are shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Recently, Fujita and co-workers have demonstrated that the Pd 6 L 4 nanocages can trap group VIII di-ruthenium carbonyl complexes. 9,11 The group VIII di-metal carbonyl complexes are well known for their interesting photochemistry [12][13][14] and catalytic properties 15 in addition to their fluxional behavior where they exist as multiple isomers in dynamic equilibrium. [15][16][17][18][19] When encapsulated by the Pd 6 L 4 nanocage, the di-ruthenium carbonyl complexes were stabilized in their cis-bridging isomeric form 9 and were shown to undergo carbonyl photosubstitution without cleavage of the metal-metal bond 11 .…”
mentioning
confidence: 99%
“…Metal-directed self-assembled coordination cages can form nanosized cavities that can act to trap and stabilize guest molecules through noncovalent interactions. The physical and chemical properties of these host–guest complexes are dictated by the interplay of many factors including steric restrictions, electrostatics, and weak interactions such as π-stacking. , One such example of the self-assembled coordination cages is the octahedral Pd 6 L 4 nanocage first synthesized by Fujita and coworkers . This nanocage has been successfully employed over the last two decades to carry out selective ground and excited reactions and trap and stabilize reactive species. Recently, Fujita and coworkers have demonstrated that the Pd 6 L 4 nanocages can trap group-VIII diruthenium carbonyl complexes. , The group-VIII dimetal carbonyl complexes are well known for their interesting photochemistry and catalytic properties in addition to their fluxional behavior, where they exist as multiple isomers in dynamic equilibrium. When encapsulated by the Pd 6 L 4 nanocage, the diruthenium carbonyl complexes were stabilized in their cis-bridging isomeric form and were shown to undergo carbonyl photosubstitution without cleavage of the metal–metal bond . From analysis of the X-ray crystal structures, the stabilization was attributed to π-stacking interactions between the triazine walls of the cage and the cyclopentadienyl ligands of the metal carbonyl complexes, and the photochemical products were suggested to arise from the restricted dynamics of the guests within the cage .…”
mentioning
confidence: 99%
See 2 more Smart Citations